The Western Front diaries the ANZACs' own story, battle by battle - King, Jonathan 1942- (Simon & Schuster Australia, 2008)
"Using hundreds of brutally honest and extraordinary eyewitness accounts of the diggers in the muddy and bloody trenches, Western Front Diaries reproduces their private diaries, letters and postcards to tell of their heart-rending experiences, battle by bloody battle. Written chronologically, this book reveals the little-known Australian achievements on the Western Front."--Provided by publisher.